PET imaging of atherosclerosis. (January 2015) - Tarkin, Jason M; Joshi, Francis R; Rajani, Nikil K; Rudd, James HF
ABSTRACT : Atherosclerosis is a chronic, progressive, multifocal disease of the arterial wall, which is mainly fuelled by local and systemic inflammation, often resulting in acute ischemic events following plaque rupture and vessel occlusion. When assessing the cardiovascular risk of an individual patient, we must consider both global measures of disease activity and local features of plaque vulnerability, in addition to anatomical distribution and degree of established atherosclerosis. These parameters cannot be measured with conventional anatomical imaging techniques alone, which are designed primarily to identify the presence of organic intraluminal obstruction in symptomatic patients. However, molecular imaging with PET, using specifically targeted radiolabeled probes to track active in vivo atherosclerotic mechanisms noninvasively, may potentially provide a method that is better suited for this purpose. Vascular PET imaging can help us to further understand aspects of plaque biology, and current evidence supports a future role as an emerging clinical tool for the quantification of cardiovascular risk in order to guide and monitor responses to antiatherosclerosis treatments and to distinguish high-risk plaques.